Christian Spirituality and Praxis in Africa: The Role of Spiritual Guides (Hekima Review, 2025)
Africans are generally viewed as religious. However, the level at which this reflects and affects their lifestyle and well-being leaves much to be desired. It often calls to question whether their religion is merely worship without translation into their relationship with others and their living condition. This paper limits itself to only the spirituality of the Christian religion, one of the religions that has gained widespread acceptance in Africa. Despite this fact, the praxis of its spirituality among Christians is not proportionate to itslevel of spread. In order to address this issue, the paper explores the role of Spiritual guides, bringing out their importance in the direction of achieving the desired level of its praxis. It holds that the onus falls very much on the spiritual guides through the proper discharge of their duties to realise the desired praxis of Christian spirituality.